Occupational Health and Safety in Tech-Based Employment - Pisarczyk, Łukasz (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The article discusses the impact of modern technologies on the safety of the work process. The author indicates areas in which the technology (remote communication means, artificial intelligence algorithms) may threaten workers’ broadly understood safety. The author suggests problems such as excessive workload, difficulties in effectively using the right to rest, or isolation of employees. He emphasizes the need to ensure protection for workers. From this perspective, he assesses the existing legal framework and formulates conclusions for the future (e.g., the right to disconnect). He refers to supranational standards, European Union law, and national regulations.